Genotypic and phenotypic associations of yield related traits in barley genotypes - Jalata, Zerihun (Journal of Pure and Applied Agriculture, 2023)
The knowledge of the nature of associations existing among different component traits is basic to conduct effective selection. Thus, a field experiment was conducted on 28 barley genotypes in randomized block design arrangement with three replications at Holeta in the 2015 season to examine the existing interrelationship between desirable characters including yield barley. The data was recorded on heading date, maturity date, seed filling period, height, effective or tillers plant-1 , flag leaf area, spike length, kernel number per spike, seed weight, biomass weight plant-1 , grain yield plant-1 and harvest index plant-1 . Thus, the result indicated most of the relationships in phenotypic and genotypic terms between the desirable characters were positive and significant showing the need to examine the most yield influencing characters for selection. The relationship among every character also showed most of the quantitative characters were influenced by the interaction of several characters. Moreover, the path analysis result of biomass yield and harvest index characters showed a direct strong influence on yield in the positive direction and at the same time, these characters had a highly positive association with grain yield indicating as major contributors of yield. Thus, in general, the finding reveals that both biomass yield and harvest index plant-1 characters had a true relationship with barley grain yield implying some amount of improvement in one or both characters will directly contribute to an increased yield. While increased biomass provides additional animal feed. © 2021 Department of Agricultural Sciences, AIOU